Exploring syntactic complexity and its relationship with writing quality in EFL argumentative essays - Elias, Wondemagegne; Birhanu, Simegn; Ebabu, Tefera Adugna (Journal of Language Research, 2024)
Despite a large number of studies examining syntactic features that are predictive of second language (L2) writing quality, assessed by human raters at the university level, few have systematically investigated this link using a large set of indices in the foreign language learning (EFL) classroom context. The current study sought to determine the extent to which a variety of syntactic complexity and sophistication indices are associated with and may predict writing quality by analyzing 30 argumentative essays written by undergraduate EFL students in an Ethiopian university classroom setting. To represent syntactic complexity as a multidimensional construct, we used conventional absolute measures, fine-grained clausal and phrasal indices, and newly proposed sophistication indices related to the use of verb argument constructions (VACs) indexed by TAASSC (Tool for the Automatic Analysis of Syntactic Sophistication and Complexity; 17. Essays were graded, and five separate predicted models of writing quality were created utilizing each complex feature index and all of the measures. Robust predictors of writing quality were identified at both syntactic complexity and sophistication dimensions. Regression analyses showed that the combined model including both fine-grained clausal complexity and VAC-based indices could account for 53.6% of the variance (the largest amount of variance in the study) in writing scores. The finding indicates that the inclusion of diversified adverbial modifiers and nonfinite clauses such as modal auxiliaries controlled by less frequent verbs were predictive of higher-quality writing. These findings shed light on some characteristics of L2 learners' writing growth and enable us to draw pedagogical implications for teaching and assessing writing in the Ethiopian EFL context.
Keywords: Syntactic complexity; Syntactic sophistication; Verb argument constructions; EFL writing quality